2019
DOI: 10.31685/kek.v3i1.463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Dinamis Dampak Fiskal Otonomi Khusus terhadap Efisiensi Layanan Publik Dan Pertumbuhan Ekonomi di Provinsi Papua, Papua Barat dan Aceh Tahun 2011-2017

Abstract: AbstrakPenelitian ini menganalisis dampak fiskal Otonomi Khusus (Otsus) Provinsi Papua, Papua Barat, dan Aceh terhadap efisiensi pemberian layanan publik, serta implikasinya pada pertumbuhan PDRB per kapita, dengan metode Data Envelopment Analysis (DEA) dan model estimasi Dynamic Generalized Method of Moment (DGMM). Hasil penelitian menunjukkan, bahwa di tingkat provinsi dan kabupaten/kota, penerimaan Otsus berpengaruh negatif pada efisiensi belanja pendidikan, kesehatan, dan infrastruktur publik, namun terhad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 6 publications
0
10
1
11
Order By: Relevance
“…Furthermore, based on potential improvement, Aceh is a province with the lowest potential improvement with 12 red columns and only 2 green columns. However, these results differ from the findings of a study conducted by Widodo (2019), which shows that Aceh is a province that is relatively efficient in managing education spending and has an efficiency value of spending on public services and public services above the average efficiency value of the province nationally.…”
Section: Resultscontrasting
confidence: 99%
“…Furthermore, based on potential improvement, Aceh is a province with the lowest potential improvement with 12 red columns and only 2 green columns. However, these results differ from the findings of a study conducted by Widodo (2019), which shows that Aceh is a province that is relatively efficient in managing education spending and has an efficiency value of spending on public services and public services above the average efficiency value of the province nationally.…”
Section: Resultscontrasting
confidence: 99%
“…Studies regarding the impact of decentralization in the regional scope are still considered minimal so it is deemed necessary to carry out further research. Previous research also found that the realization of regional government budgets in many regions is dominated by personnel spending rather than capital and development spending (Haryanto, 2019), regional spending tends to be inefficient and increases in local government revenues are not accompanied by improvements in public services (Widodo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The fairly large fiscal implications accompanied by full discretion in its management should be a stimulus for Aceh Province to increase regional spending to support the provision of public goods and services, development of infrastructure and public facilities, especially in the fields of education, health and economic growth. This is very necessary so that Aceh Province can catch up with the progress of other regions in Indonesia and accelerate efforts to improve community welfare, which is the main goal of special autonomy and asymmetric decentralization (Widodo, 2019). Theoretically, the implementation of Special Autonomy within an asymmetric decentralization framework should be able to increase the efficiency of better public services (Widodo, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations